1993
DOI: 10.1111/j.1432-2277.1993.tb00747.x
|View full text |Cite
|
Sign up to set email alerts
|

Visceral leishmaniasis after orthotopic liver transplantation: impact of persistent splenomegaly

Abstract: Visceral leishmaniasis was observed in a 50-year-old female liver transplant recipient 1 year following transplantation. Signs of active infection were low-grade fever, pancytopenia, persistent splenomegaly, positive cultures for leishmania in liver and bone marrow biopsy specimens, and newly positive leishmania serology. Following sequential therapy with pentavalent antimony and amphotericin B, blood values improved massively, bone marrow cultures became negative, and leishmania serology decreased. Secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…In our case and the one of Shamar et al [3], we were able to find 17 cases of VL in solid organ recipients [3][4][5]. Except for 1 liver transplant recipient [5], all were renal transplant recipients.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In our case and the one of Shamar et al [3], we were able to find 17 cases of VL in solid organ recipients [3][4][5]. Except for 1 liver transplant recipient [5], all were renal transplant recipients.…”
Section: Discussionsupporting
confidence: 52%
“…Except for 1 liver transplant recipient [5], all were renal transplant recipients. The majority of the patients lived or had traveled to areas where VL is endemic, including Southern Europe, Malta, the Near East and India.…”
Section: Discussionmentioning
confidence: 99%
“…Visceral leishmaniosis after organ transplantation has been described on some 26 occasions, mostly in renal patients 8,9 and, to the best of our knowledge, ours is only the third case following liver grafting. 10,11 The mortality is high, as Berenguer et al reported five deaths out of 18 patients.…”
Section: Objectif : L'infection Récurrente Au Cytomégalovirus (Cmv) Estmentioning
confidence: 88%
“…Over 60 cases of VL in SOT recipients have been described (14,27,136,164,176,184,251,274,319,342), with the majority occurring in renal transplant patients. This correlates with the increased number of renal transplants performed compared to other organs.…”
Section: Infections Caused By Leishmania Sppmentioning
confidence: 99%